2020
DOI: 10.3390/cancers12030526
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Crizotinib, Ceritinib, and Alectinib in ALK-Positive Non-Small Cell Lung Cancer Treatment: A Meta-Analysis of Clinical Trials

Abstract: This study aimed to evaluate the efficacy of anaplastic lymphoma kinase (ALK)-inhibitors in the treatment of ALK-positive non-small cell lung cancer (NSCLC) by using a meta-analysis of clinical trials. We searched PubMed, EMBASE, Cochrane Library, and Clinicaltrials.gov by using keywords related to the topic in August 2018. The pooled effect sizes were calculated based on a random-effects model. We also performed subgroup meta-analysis by types of ALK inhibitors (crizotinib, ceritinib, and alectinib). A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Consequently, it is not possible with our study design to affirm whether there is any real benefit of using crizotinib in improving OS in this patient population. The finding results are aligned with other systematic reviews and meta-analyzes identified during the literature search [27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consequently, it is not possible with our study design to affirm whether there is any real benefit of using crizotinib in improving OS in this patient population. The finding results are aligned with other systematic reviews and meta-analyzes identified during the literature search [27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, we wanted to provide baseline data for any subsequent evaluation of therapies for NSCLC patients with [26]. We believe this is the first systematic review and meta-analysis to summarize the scientific evidence on the use of this drug exclusively in the first line of treatment for NSCLC ALK?, building on previous publications [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Although ceritinib is also a second-generation ALK inhibitor, our study showed that there is no signicant difference in the efficacy between ceritinib and crizotinib. Similarly, the recent meta-analyses of pooled estimates reported that crizotinib might have higher ORR [66% (58-74%) vs. 52% (38-66%)] and longer PFS [9.27 months (8.28-10.26) vs. 5.92 months (4.36-7.48)] than ceritinib, although no statistical test was performed [26]. It remains unclear why ceritinib did not show a superior efficacy unlike alectinib.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Crizotinib, an oral ALK/MET/ROS1 inhibitor, prompted the development of ALK target therapy[ 90 ]. It became the first ALK inhibitor to be approved by the FDA for standard first-line therapy in patients with ALK-positive NSCLC.…”
Section: Closing Remarks and Future Perspectivementioning
confidence: 99%